Microfiltration of algae (Chlorella sorokiniana) : critical flux, fouling and transmission - Wicaksana, Filicia (2013)
Fouling and transmission studies of algae broth (Chlorella sorokiniana) during cross-flow microfiltration were performed using direct microscopic observation technique. The flux stepping test was conducted for approximately 15 min interval and images were captured at the beginning and at the end of each flux step for further analysis of membrane surface coverage. The rate of membrane surface coverage was correlated to the rate of transmembrane pressure (TMP) rise. Results suggested that Direct Observation Through the Membrane (DOTM) technique was more sensitive to indicate the membrane fouling than TMP monitoring method. Deposition of microalgal cells started to occur even at a very low permeate flux. The layer of algal cells would eventually build up and might result in severe fouling. Despite this early deposition, TMP values remained low and would only increase when the fouling had become more pronounce.